Impact of the Daberas slimes dam in southern Namibia on the water quality of the Orange River - Ailonga, Chris Elungi (My University, 2011)
Daberas slimes dam has been seeping since 2004. As a result, seepage leachate could have been passing through a permeable layer of gravel from the slimes dam to an international river. This was a major concern especially from department of Water Affairs and the Ministry of Mines and Energy in Namibia. The main concern was the possible water contamination of the Orange River, which of course leads to the Orange River mouth, which is a Ramsar protected site and the other concern was that the trees along the riverbank section that is adjacent to the Daberas tailings dam were dying. This study has however revealed that the seepage leachate from the Daberas slimes dam is actually reaching the Orange River. Given limited available results, a minor impact on the water quality of the river has been recorded. All parameters that were studied are well within the limit of excellent water quality, with respect to the current water guidelines in Namibia. Iron and manganese which are components of ferrosilicon which is used as Dense Medium Separation (DMS) material at Daberas remains well within the limit of excellent water quality as per Namibian water guidelines. Most interestingly, the latest sample analysis confirms that iron concentration in water is actually declining near the Daberas mine section, meaning that iron concentration is higher in the upstream section in the latest samples taken in July 2007. The water quality in the Orange River section downstream of Daberas mine is Arated, characterising water with excellent quality, as per Namibian water guidelines. Despite that, an effective integrated water management plan and concise water-monitoring plan is recommended for the Daberas mine.